Implementasi Sistem Pendukung Keputusan Geografis untuk Penempatan Cabang Dealer dengan Simple Additive Weighting - Astria Hijriani; Claudia Cindy Owen; Anie Rose Irawati (MULTINETICS, 2026)
Determining a new dealer branch location is a strategic decision that requires careful consideration of spatial, demographic, competitive, and operational factors. PT Tunas Dwipa Matra, as an official Honda motorcycle main dealer in Bandar Lampung, needs a decision support system that can assist management in evaluating and ranking alternative branch locations objectively. This study develops a web-based geographic decision support system by applying the Simple Additive Weighting method to calculate the preference value of each candidate location. The assessment uses seven criteria, namely rental cost, number of nearby workshops, number of nearby showrooms, road type, distance from the nearest Honda dealer, number of markets, and population. These criteria are processed through weighting, normalization, and ranking stages to produce the best location recommendation. Spatial information is presented through a Web-GIS interface, while survey data are collected using an Android application connected to the database through a web service. The system development process includes requirement analysis, manual calculation, system design, implementation, and testing. Functional testing using equivalence partitioning shows that the main system features operate according to user requirements. Decision testing also indicates that the system can generate structured recommendations and support managers in comparing alternative locations more transparently, systematically, and efficiently.